Advantages and disadvantages of hog marketing groups - Mintert, J.; Tynon, R.; Tokach, Michael D.; Langemeier, Michael R.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ten hog marketing groups located in Kansas and Iowa were surveyed during 1993 to determine the success, operation, and management of hog marketing groups. Marketing group leaders were asked to identify principal advantages and disadvantages of marketing hogs in groups. Survey responses indicated that marketing hogs in groups led to producers receiving higher sale prices for their hogs and helped reduce their marketing costs. Commonly cited disadvantages of group marketing, included a loss in marketing flexibility, difficulties in coordinating loads among group members, and concerns about increased susceptibility to diseases from other herds.
Keywords: Swine; Hog marketing groups